The Relationship Between Service Quality and Buddhists Satisfaction Towards Buddhists Interest in Depositing Ancestors' Nameboards (A Case in Ksitigarbha Sala Vihara Dharma Agung Makassar) - Frengky Fonso; Dali Santun Naga; Hastho Bramantyo (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
Ksitigarbha Sala Vihara Dharma Agung Makassar is one of the vihara that provides ancestral nameplate storage services. In carrying out this service, service quality and Buddhists satisfaction are important factors that influence the interest of the Buddhists to entrust ancestral nameplates. This study aims to analyze the relationship between service quality and Buddhists satisfaction with the interest of the Buddhists to entrust ancestral nameplates at Ksitigarbha Sala Vihara Dharma Agung Makassar. The research method used is quantitative with an associative approach. The population in this study were Buddhists who entrust ancestral nameplates, with a simple random sampling technique so that a sample of 100 respondents was obtained. The data analysis technique in this study used descriptive statistical analysis and explanatory correlation. The results of this study indicate a positive and significant relationship between service quality (X1) and Buddhists interest (Y) and a positive and significant relationship between Buddhists satisfaction (X2) and Buddhists interest (Y). There is also a positive and significant relationship between service quality (X1) and Buddhists satisfaction (X2) and Buddhists interest (Y) in entrusting ancestral nameplates (A case at Ksitigarbha sala, Vihara Dharma Agung, Makassar).